Agricultural sustainability in Karnataka: Application of Sustainable Livelihood Security Index - BEERALADINNI, DEVENDRA; PATIL, B L (The Indian Journal of Agricultural Sciences, 2023)
The present study was carried out in Karnataka state to assess the relative agricultural sustainability status of Karnataka during the year 2021–22 using Sustainable Livelihood Security Index (SLSI). Three indicators, viz. Ecological Security, Economic Efficiency and Social Equity Index were used. The results of the study show that in Karnataka better conditions for sustainable agriculture exist in majority of the Southern districts. However, few Northern districts, viz. Belagavi, Raichur, Bagalkote and Ballari have better level of ecological security and some Southern districts Bengaluru (U), Bengaluru (R), Chikkaballapur, Kolar and Ramanagara have low level of ecological security. In economic efficiency and social equity indicator also, majority of the Northern districts lagged behind compared to southern districts while Belagavi and Kalburgi districts have shown better performance compared to rest of the districts in the state. Adoption of sustainable agricultural practices such as judicial use of fertilizers and plant protection chemicals, efficient water use techniques (drip and sprinkler irrigation), use of organic manures and diversification of farm activities would help in sustainable agricultural development. To achieve ecological sustainability, steps need to be taken to enhance forest cover through afforestation especially in the districts which have poor ecological security. Further, there is a need to enhance the crop yield, encourage dairy farming and improve work force participation through training and skill development in the districts with poor economic efficiency.